Development and characterization of irradiated-corn-starch films. (15th August 2018) - Li, Li; Chen, Hongpu; Wang, Min; Lv, Xiaolan; Zhao, Yongfu; Xia, Liru
Highlights: Gamma ray irradiation decreased the crystallinity of starch. Gamma ray irradiation decreased the distribution of larger starch particles. Higher irradiation doses increased the tensile strength of starch films. Higher irradiation doses decreased the water vapor permeability of starch films. Abstract: The effect of 60 Co gamma ray irradiation on the physicochemical and crystalline properties of native corn starch were investigated. Fourier transform infrared spectroscopy and X-ray diffraction showed that irradiation had a slight effect on the molecular structure of corn starch with crystallinity decreasing with increasing irradiation dose. Particle size analysis showed that 59.1% of native corn starch granules had sizes of ≥8 μm, which decreased to only 24.1% after treatment with an irradiation dose of 40 kGy. Irradiated-corn-starch films were prepared by casting gelatinized irradiated-corn-starch solutions. An increased irradiation dose was found to increase the tensile strength of the resultant films, but caused a significant decrease in water vapor permeability. The irradiated-corn-starch films showed potential for the development of biodegradable starch films with improved properties.